KONSEP TEOLOGI PLURALISME GUS DUR DALAM MERETAS KEBERAGAMAN DI INDONESIA - Setiawan, Eko (ASKETIK: Jurnal Agama dan Perubahan Sosial, 2017)
Abdurrahman Wahid, who is familiar with Gus Dur is a thinker and a fighter for democracy, pluralism,prominent anti violence, defend those who are marginalized and protector of religious minorities, gender, creed,ethnicity and even among themselves. Gus Dur and pluralism are two things that are difficult to separate. Heis a figure who is very concerned with diversity, difference and diversity. Included in the religious life. In fact,he is also close to the leaders of religions other than Islam that he holds. Often go out into a place of worship ofother religions. This is what often leads to misinterpretation of pluralism that Gus Dur teach. But after his death,December 30, 2009 and then, people started to realize the truth about how tolerant he preaches. Pluralism istaught Gus Dur is purely of clear thinking and is based on the Quran and the Hadith of the Prophet.Keywords: Pluralism, Gus Dur, diversity, Islam, Indonesia